Curvularia coatesiae XK8, a Potential Bioadsorbent Material for Adsorbing Cd(II) and Sb(III) Compound Pollution: Characteristics and Effects - Di, Zhao; Chaoyang, Li; Mengxi, Zheng; Yunlin, Zhao; Zhenggang, Xu; Guiyan, Yang (Frontiers in Microbiology, 2022)
Soil heavy metal pollution is a common problem in mining areas. The soil of the Xikuangshan located in Lengshuijiang, Hunan Province, China contains various excessive heavy metals, especially antimony and cadmium. Previous studies have shown that heavy metal-tolerant microorganisms screened from mining areas have the potential to adsorb heavy metals. In this study, we screened out a cadmium and antimony tolerant fungus named XK8 from the slags collected from the Xikuangshan. Then, we explored the single and binary biosorption characteristics of Cd(Ⅱ) and Sb(Ⅲ) on it. In our results, the fungus XK8 was identified as Curvularia coatesiae XK8 by ITS sequencing analysis. Under the optimal conditions, in binary biosorption of the XK8, the main effect of the initial cadmium concentration on the cadmium removal rate of XK8 is negative, while the main effect of the initial antimony concentration, biosorption time and initial pH on the cadmium removal rate of XK8 is positive. The initial pH has the greatest impact on the biosorption of cadmium on XK8, followed by the biosorption time, moreover, the effects of both are stronger than the coexisting ions. SAS analysis shows that under the optimal conditions, the theoretical maximum cadmium removal rate of XK8 is 100%, and the actual removal rate is 67.57%. Compared the single biosorption with binary biosorption, the maximum biosorption capacity of XK8 for cadmium in the composite biosorption system increased to 23.6 mg g-1. It shows that under the background of high antimony, Sb(Ⅲ) has a promoting effect on the biosorption of Cd(Ⅱ) on XK8. In summary, a cadmium and antimony tolerant fungus with strong cadmium biosorption ability under the background of high antimony was screened out. It provides a potential microbial material for the bioremediation of heavy metal pollution.